Impaired awareness of action-outcome contingency and causality during healthy ageing and following ventromedial prefrontal cortex lesions. (May 2019) - O'Callaghan, Claire; Vaghi, Matilde M.; Brummerloh, Berit; Cardinal, Rudolf N.; Robbins, Trevor W.
Abstract: Detecting causal relationships between actions and their outcomes is fundamental to guiding goal-directed behaviour. The ventromedial prefrontal cortex (vmPFC) has been extensively implicated in computing these environmental contingencies, via animal lesion models and human neuroimaging. However, whether the vmPFC is critical for contingency learning, and whether it can occur without subjective awareness of those contingencies, has not been established. To address this, we measured response adaption to contingency and subjective awareness of action-outcome relationships in individuals with vmPFC lesions and healthy elderly subjects. We showed that in both vmPFC damage and ageing, successful behavioural adaptation to variations in action-outcome contingencies was maintained, but subjective awareness of these contingencies was reduced. These results highlight two contexts where performance and awareness have been dissociated, and show that learning response-outcome contingencies to guide behaviour can occur without subjective awareness. Preserved responding in the vmPFC group suggests that this region is not critical for computing action-outcome contingencies to guide behaviour. In contrast, our findings highlight a critical role for the vmPFC in supporting awareness, or metacognitive ability, during learning. We further advance the hypothesis that responding to changing environmental contingencies, whilst simultaneously maintaining conscious awareness of those statistical regularities, is a form of dual-tasking that is impaired in ageing due to reduced prefrontal function. Highlights: In both vmPFC lesions and ageing, intact responding to variations in action-outcome contingencies was maintained. In contrast, vmPFC damage and ageing impaired subjective awareness of action-outcome contingencies. vmPFC is not critical for contingency learning. vmPFC has a critical role in supporting awareness (metacognition) during learning. Impaired causal awareness in ageing may result from dual-tasking costs.